Characteristics of Adolescents with Pre-Metabolic Syndrome - Septiany, Maulidya; Dhian Ririn Lestari; Mutia Rahmah (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2025)
Metabolic syndrome is a cluster of metabolic disorders characterized by central obesity, elevated blood pressure, impaired glucose tolerance, insulin resistance, and increased triglyceride and LDL cholesterol levels. In 2017, the World Health Organization (WHO) stated that cardiovascular disease, a major manifestation of metabolic syndrome, was the leading cause of death globally. In Indonesia, the prevalence of metabolic diseases has also increased, particularly among children and adolescents, due to poor lifestyle habits. This study aimed to describe the characteristics of adolescents with metabolic syndrome. The study employed a quantitative descriptive design. Data were collected through anthropometric measurements, physical examinations, and blood sampling. Descriptive statistical analysis was used to analyze the data. The results showed that the average age of respondents was 16 years, the majority were female (53.3%), none had a history of drug use (100%), most did not smoke (56.7%), and most were in a pre-metabolic syndrome condition (90%). Additionally, 73.3% had normal blood pressure, 100% had normal random blood glucose levels, 60% had normal triglyceride levels, LDL cholesterol levels were normal, HDL cholesterol was normal in 93.3% of respondents, and 63.3% were categorized as underweight based on Body Mass Index (BMI).